Internationalizing higher education in Nigeria: Essential tool for social and economic development - Muhammad, Ibrahim Garba; Abdullah, Haim Hilman; Ibrahim, Najafi Auwalu (2017)
This conceptual paper highlights the significance of internationalizing higher education as a global phenomenon and discusses some of the potentials for developing nations with specific reference to Nigeria. The paper also dwell on examining Malaysia’s commitment to internationalization, the contributions it makes in the educational sub sector as well as the role it plays in the nation’s social and economic development.The paper concludes by discussing implications of the internationalization policy, benefits and suggests some measures that can positively contribute to effective implementation of the policy in the developing world.